STATISTIČKI POKAZATELJI ZA NEZGODE NA RADU U POLJOPRIVREDNOM SEKTORU - Mitrevski, Vangelče (Journal on Processing and Energy in Agriculture, 2023)
The agricultural activity employs an estimated 1.3 billion workers worldwide, that is half of the world’s labour force. In terms of fatalities, injuries and work-related ill-health, it is one of the four most hazardous sectors of activity (along with construction, transportation and storage and manufacturing). According to ILO estimates, at least 170000 agricultural workers are dead each year. In this paper the statistical indicators concerning non-fatal and fatal accidents at work in agriculture, forestry and fishing activity and an incidence rates in the Member State on European Union (EU-27) and in the R.N. Macedonia during 2017÷2021 were presented. The performed statistical analysis shows that the number of non-fatal and fatal accidents at work in agriculture, forestry and fishing activity in EU-28, in 2020 was decreased in comparison with 2017. In the R.N. Macedonia in 2021 there was a decrease in the number of non-fatalaccidetns at work in comparison with 2017. During on 2021 in the R.N. Macedonia there were no recorded fatal accidents at work. This fact categorizes the R.N. Macedonia in the category of EU-27 Member States with zero fatal accidents at work.